The clinical features, muscle pathology, and role of autophagy in anti-Ku-positive patients - Qiao, Lingya; Lin, Ying; Liu, Mengyang; Liu, Jiaqi; Li, Ke; Chen, Juan; Shi, Qiang (Frontiers in Immunology, 2025)
AimsThis study aimed to examine the clinical and muscle histological characteristics of anti-Ku-positive patients. A preliminary investigation into the involvement of autophagy was conducted as well.MethodsClinical characteristics, laboratory findings, and muscle histological features were collected from patients with isolated anti-Ku antibodies at the Department of Neurology, First Medical Center of the PLA General Hospital, between February 2011 to June 2024. Autophagy-related protein levels were semi-quantitatively assessed on muscle tissue samples using western blot (WB), with sporadic inclusion body myositis (sIBM) and immune-mediated necrotizing myopathy (IMNM) patients as comparison groups.ResultsA total of 6 patients were recruited in the study (50% female, mean age at onset 47.6 ± 15.56 years, mean disease duration 7 ± 5.58 months). Extramuscular involvement was observed in most cases, including subcutaneous edema (33.3%), skin rash (33.3%), hyperpigmentation (33.3%), hair loss (33.3%), arthralgia (50%), and interstitial lung disease (ILD) (33.3%), etc. Coexisting connective tissue diseases included systemic sclerosis (SSc) (83.3%), systemic lupus erythematosus (SLE) (16.7%), and arthritis (16.7%). The distribution of muscle weakness was generally symmetrical and proximal (83.3%). Distal (50%) and axial (50%) muscle weakness could also be found. 2 patients exhibited peripheral nerve damage and myogenic damage in EMG, while 4 showed myogenic damage. Creatine kinase (CK) was mildly or moderately elevated. Muscle biopsy demonstrated two patterns: a neurogenic atrophy pattern and a myositis pattern characterized by a varying degree of necrotizing fibers (100%) with rimmed vacuoles (50%) or non-rimmed vacuoles (50%). Immunohistochemical (IHC) analysis revealed sarcolemma deposition of major histocompatibility complex class I (MHC-I) (83.3%) and MHC-II (83.3%), as well as predominant CD68-positive inflammatory infiltrates (66.7%). IHC for p62 revealed a sarcoplasmic punctate pattern (50%), along with a focal coarse staining pattern (50%) and occasional fine granular staining (33.3%). Electron microscopy (EM) demonstrated filamentous and lipid accumulation within vacuoles. WB analysis showed that p62 levels significantly differed between the anti-Ku and IMNM groups. Additionally, Parkin levels were highest in sIBM, while lysosome-associated membrane protein 2 (LAMP2) and microtubule-associated protein 1A/1B-light chain 3 (LC3) expression was highest in the anti-Ku-positive group in tendency.ConclusionThe muscular features were heterogeneous in anti-Ku-positive patients. A predominant myositis pattern was characterized by necrotizing fibers and vacuolar changes in muscle histology, which differ from sIBM and IMNM. Autophagy appeared to be a key mechanism implicated in the pathogenesis.